Faces of God - Mumtaz, Murad Khan, 1980- (Leiden ; Boston)
xxv, [1] sayfa, [1] sayfa harita, 378 sayfa
Keywords: “Islamic art is often misrepresented as an iconophobic tradition. As a result of this assumption, the polyvalence of figural artworks made for South Asian Muslim audiences has remained hidden in plain view. This book situates manuscript illustrations and album paintings within cultures of devotion and ritual shaped by Islamic intellectual and religious histories. Central to this story are the Mughal siblings, Jahanara Begum and Dara Shikoh, and their Sufi guide Mulla Shah. Through detailed art historical analysis supported by new translations, this study contextualizes artworks made for Indo-Muslim patrons by putting them into direct dialogue with written testimonies“ --